Fabrication of nylon-6,6 membranes coated with violacein pigment for wound dressing application - Siti Hajar Osman, 1995-, author; Siti Aminah Setu @ Sabtu, 1987-, supervisor; Fakulti Sains (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Project Paper (Sarjana Muda Sains (Kimia)) - Universiti Teknologi Malaysia, 2018